Bevacizumab with or after chemotherapy for platinum-resistant recurrent ovarian cancer: exploratory analyses of the AURELIA trial. (8th May 2017) - Bamias, A.; Gibbs, E.; Khoon Lee, C.; Davies, L.; Dimopoulos, M.; Zagouri, F.; Veillard, A.-S.; Kosse, J.; Santaballa, A.; Mirza, M. R.; Tabaro, G.; Vergote, I.; et al.
Abstract: Background: In the open-label randomized phase III AURELIA trial, adding bevacizumab to chemotherapy for platinum-resistant ovarian cancer (PROC) significantly improved progression-free survival and response rate versus chemotherapy alone, but not overall survival (OS). We explored the effect of bevacizumab use after disease progression (PD) in patients randomized to chemotherapy alone. Patients and methods: In AURELIA, 361 women with PROC were randomized to chemotherapy alone or with bevacizumab. Patients initially randomized to chemotherapy were offered bevacizumab after PD. Post hoc analyses assessed efficacy and safety in three subgroups: chemotherapy alone, chemotherapy followed by bevacizumab after PD, and chemotherapy plus bevacizumab at randomization. Results: Of the 182 patients randomized to chemotherapy alone, 72 (40%) received bevacizumab after PD and 110 (60%) never received bevacizumab. There were no significant differences in patient and disease characteristics between these subgroups at baseline or the time of PD. Compared with patients never receiving bevacizumab, the risk of death was significantly reduced in patients receiving bevacizumab either upfront with chemotherapy [hazard ratio (HR) = 0.68, 95% confidence interval (CI) 0.52–0.90] or after PD (HR = 0.60, 95% CI 0.43–0.86). The tolerability of bevacizumab was similar with administration upfront or after PD. Conclusions: Post-PD bevacizumab use may have confounded OS results in AURELIA. In these exploratory analyses of non-randomized subgroups, bevacizumab use, either with chemotherapy or after PD on chemotherapy alone, improved OS compared with no bevacizumab. Combining bevacizumab with chemotherapy at first appearance of platinum resistance maximises the likelihood of patients receiving this active treatment for PROC. ClinicalTrials.gov: NCT00976911.